Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1038/sj.ejcn.1601539
|View full text |Cite
|
Sign up to set email alerts
|

Lack of benefit of dietary advice to men with angina: results of a controlled trial

Abstract: Objective: To see whether mortality among men with angina can be reduced by dietary advice. Design: A randomized controlled factorial trial. Setting: Male patients of general practitioners in south Wales. Subjects: A total of 3114 men under 70 y of age with angina. Interventions: Subjects were randomly allocated to four groups: (1) advised to eat two portions of oily fish each week, or to take three fish oil capsules daily; (2) advised to eat more fruit, vegetables and oats; (3) given both the above types of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
260
5
15

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(287 citation statements)
references
References 26 publications
6
260
5
15
Order By: Relevance
“…They also failed to distinguish any specific effects of consuming oily fish or fish oil supplements. The outcome of this analysis has sparked considerable debate, especially the concern regarding the inclusion of the Diet and Angina Randomized Trial (DART-2) by Burr et al (2003), which reported adverse effects of increasing oily fish consumption/fish oil supplements in patients suffering from angina. This trial has been criticized as being unblinded and for the nature of the EPA-rich fish oil (Marik and Varon, 2009).…”
Section: Long Chain N-3 Pufa and Cvdmentioning
confidence: 99%
“…They also failed to distinguish any specific effects of consuming oily fish or fish oil supplements. The outcome of this analysis has sparked considerable debate, especially the concern regarding the inclusion of the Diet and Angina Randomized Trial (DART-2) by Burr et al (2003), which reported adverse effects of increasing oily fish consumption/fish oil supplements in patients suffering from angina. This trial has been criticized as being unblinded and for the nature of the EPA-rich fish oil (Marik and Varon, 2009).…”
Section: Long Chain N-3 Pufa and Cvdmentioning
confidence: 99%
“…• prospective cohorts -Yes [34,[51][52][53][54][55][56][57][58][59][60][61]; No [62] • case-control studies -Yes [63,64]; No [62,65] • Raising biomarker levels with fish or omega-3 FAs reduces risk -Yes [66,67]; No [68] • Strong association between biomarker and disease -Yes [34] • Biomarker independent of other known risk factors -Yes [33,34,59] • Adds predictive value to currently-available risk markers -Unknown …”
mentioning
confidence: 99%
“…of cardiovascular mortality in high-risk and general populations [1], although recent trials [2,3] and a metaanalysis [4] have cast doubt on the strength of this evidence. There are limited data about the potential benefits for people with type 2 diabetes [5,6], but two prospective cohort studies among women showed that the risk of coronary heart disease is much lower among women with type 2 diabetes who consume n-3 PUFA [5,7].…”
mentioning
confidence: 99%